Negative electrode material and preparation method thereof, negative electrode plate, battery and electronic device
By constructing a stable artificial SEI film on the surface of hard carbon materials and performing in situ electrical polymerization with 2,2-dimethylvinylboric acid, the problems of irreversible capacity loss of hard carbon materials in sodium ion batteries and instability of SEI films in sodium ion batteries are solved, significantly improving the cell cycle stability and first-time Coulomb efficiency.
Patent Information
- Application Number
- CN202411767788.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-18
AI Technical Summary
When hard carbon is used as the negative electrode material of sodium ion batteries, the significant irreversible capacity loss during the first charge and discharge process and the naturally formed solid electrolyte interface (SEI) film are fragile and unstable, resulting in rapid attenuation of the battery circulation capacity.
By constructing an artificial solid electrolyte interface (SEI) film on the surface of the hard carbon material, in situ electropolymerization is carried out using 2,2-dimethylvinylboric acid to form a stable and dense polymer network layer, which acts as a barrier to prevent direct contact between the electrolyte and the hard carbon material.
It significantly reduces the irreversible capacity of hard carbon materials, improves the first Coulomb efficiency, enhances the cycle stability of the battery, and inhibits the continuous decomposition of the electrolyte.
Smart Images

Figure CN119650696A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a negative electrode material and a preparation method thereof, a negative electrode plate, a battery and an electronic device. Background Art
[0002] Given the abundant resource reserves of sodium and its excellent cost-effectiveness, sodium-ion batteries (SIBs), as a potential alternative to lithium-ion batteries, are showing unprecedented development potential. In this context, hard carbon is considered an ideal negative electrode material for sodium-ion batteries due to its large interlayer spacing, developed pore structure and abundant defect sites. However, due to the large number of pores and specific surface area of hard carbon, it suffers from significant irreversible capacity loss during the first charge and discharge process, which in turn affects the first charge and discharge efficiency. In addition, the large number of defects inside hard carbon makes the solid electrolyte interface (SEI) film naturally formed on its surface by the electrolyte fragile and unstable, and easy to rupture. During the battery cycle, this naturally generated SEI film will continue to undergo a cycle of decomposition and rupture, which will consume a large amount of active sodium ions, resulting in a rapid decay of the battery cycle capacity, which seriously restricts the application prospects of hard carbon as a negative electrode material for sodium-ion batteries.
[0003] Therefore, how to construct a stable SEI film is particularly important for improving the performance of hard carbon materials. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a negative electrode material and a preparation method thereof, a negative electrode plate, a battery and an electronic device to solve at least one problem existing in the background technology.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] A first aspect of the present invention provides a method for preparing a negative electrode material, the method for preparing a negative electrode material comprising the following steps:
[0007] S1: dissolving a hard carbon precursor in a first solvent and performing a hydrothermal reaction to obtain an intermediate A;
[0008] S2: heat-treating and pickling the intermediate A obtained in step S1 under a first protective gas atmosphere to obtain a hard carbon material;
[0009] S3: Add 2,2-dimethylvinylboric acid to the second solvent, stir for the first time, then add the hard carbon material obtained in step S2, stir for the second time, and bake to obtain the negative electrode material.
[0010] Preferably, the hard carbon precursor is selected from at least one of sucrose, glucose, maltose and starch.
[0011] Preferably, in step S1, the molar concentration of the hard carbon precursor in the first solvent is 0.2-0.5 mol / L;
[0012] Preferably, the first solvent is selected from at least one of water, methanol, ethanol, ethylene glycol, dimethylformamide and benzene;
[0013] Preferably, the temperature of the hydrothermal reaction is 150-210° C., and the time of the hydrothermal reaction is 8-15 hours.
[0014] Preferably, in step S1, after the hydrothermal reaction is completed, the steps of centrifugation, washing and drying are also included;
[0015] Preferably, the drying temperature is 60-100° C., and the drying time is 1-3 hours.
[0016] Preferably, in step S2, the first protective gas is selected from at least one of argon, helium, krypton and nitrogen;
[0017] Preferably, the temperature of the heat treatment is 1100-1600°C, and the time of the heat treatment is 3-7 hours;
[0018] Preferably, the acid washing further includes water washing and drying steps; the water washing is to neutralize the acid.
[0019] Preferably, in step S3, the mass ratio of the 2,2-dimethylvinylboric acid to the hard carbon material is (3-8):100;
[0020] Preferably, the first stirring is stirring until 2,2-dimethylvinylboronic acid is completely dissolved in the second solvent.
[0021] Preferably, in step S3, the temperature of the second stirring is 50-70° C.; the second stirring is stirring until the solution evaporates to dryness;
[0022] Preferably, the baking temperature is 80-120° C., and the baking time is 8-12 hours.
[0023] A second aspect of the present invention provides a negative electrode plate, the negative electrode plate comprising a negative electrode material, and the negative electrode material is prepared according to the preparation method of the negative electrode material according to the first aspect of the present invention.
[0024] A third aspect of the present invention provides a battery, comprising the negative electrode sheet described in the second aspect of the present invention.
[0025] A fourth aspect of the present invention provides an electronic device, comprising the battery provided by the third aspect of the present invention.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The method for preparing the negative electrode material of the present invention constructs an artificial solid electrolyte interface (SEI) film on the surface of the hard carbon material, so that it can act as a barrier to prevent direct contact between the electrolyte and the hard carbon material, thereby significantly reducing the irreversible capacity of the hard carbon material and improving its first coulombic efficiency. At the same time, the SEI film is formed by an in-situ electropolymerization reaction, and the formed artificial SEI film is stable and dense. This stable and dense SEI film can inhibit the continuous decomposition of the electrolyte, further reduce the interface impedance, and thus significantly enhance the cycle stability of the battery equipped with the negative electrode material;
[0028] (2) The preparation method of the negative electrode material provided by the present invention is simple to operate, easy to implement, can be produced on a large scale, and has broad application prospects.
[0029] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0031] Figure 1 It is a line graph comparing the capacity retention rates of the hard carbon negative electrode materials with artificial SEI films provided in Examples 1 to 4 of the present invention and the hard carbon materials provided in the comparative examples during the cycle at a rate of 0.5C / 0.5C. DETAILED DESCRIPTION
[0032] In order to make the technical scheme and beneficial effects of the present invention more obvious and easy to understand, the following is a detailed description by listing specific embodiments. Wherein, the drawings are not necessarily drawn to scale, and local features can be enlarged or reduced to more clearly show the details of local features. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually based on conventional experimental conditions. Reagents and raw materials used in the present invention are commercially available unless otherwise specified.
[0033] In the following description, a large number of specific details are given to provide a more thorough understanding of the present application. However, it is obvious to those skilled in the art that the present application can be implemented without one or more of these details. In other examples, in order to avoid confusion with the present application, some technical features known in the art are not described; that is, all features of the actual embodiments are not described here, and well-known functions and steps are not described in detail.
[0034] The purpose of the terms used herein is only to describe specific embodiments and is not intended to be limiting of the present application. When used herein, the singular forms "one", "an" and "said / the" are also intended to include plural forms, unless the context clearly indicates otherwise. It should also be understood that the terms "consisting of" and / or "comprising", when used in this specification, determine the presence of the features, integers, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, parts and / or groups. When used herein, the term "and / or" includes any and all combinations of the relevant listed items.
[0035] In order to thoroughly understand the present application, detailed steps and detailed structures will be presented in the following description to illustrate the technical solution of the present application. The preferred embodiments of the present application are described in detail below, but in addition to these detailed descriptions, the present application may also have other implementation methods.
[0036] Unless otherwise defined, technical and scientific terms used in this application have the same meanings as those in the technical field to which this application belongs.
[0037] If no specific techniques or conditions are specified in the following examples, the conventional techniques or conditions described in the literature in the art, or the conditions recommended by the product instructions and the manufacturer are generally used. The numerical ranges in the following examples all include the endpoint values.
[0038] [Method for preparing negative electrode material]
[0039] A first aspect of the present invention provides a method for preparing a negative electrode material, the method for preparing a negative electrode material comprising the following steps:
[0040] S1: dissolving a hard carbon precursor in a first solvent and performing a hydrothermal reaction to obtain an intermediate A;
[0041] S2: heat-treating and pickling the intermediate A obtained in step S1 under a first protective gas atmosphere to obtain a hard carbon material;
[0042] S3: Add 2,2-dimethylvinylboric acid to the second solvent, stir for the first time, then add the hard carbon material obtained in step S2, stir for the second time, and bake to obtain the negative electrode material.
[0043] The preparation method of the negative electrode material provided by the present invention constructs an artificial solid electrolyte interface (SEI) film on the surface of the hard carbon material, so that it can act as a barrier to prevent direct contact between the electrolyte and the hard carbon material, thereby significantly reducing the irreversible capacity of the hard carbon material and improving its first coulombic efficiency. At the same time, the unsaturated carbon-carbon double bonds on the 2,2-dimethylvinylboronic acid undergo in-situ electropolymerization during the charge and discharge process to form a polymer network. The artificial SEI film formed on the hard carbon surface is stable and dense. This stable and dense SEI film can inhibit the continuous decomposition of the electrolyte, further reduce the interface impedance, and significantly enhance the cycle stability of the battery equipped with the negative electrode material.
[0044] In certain embodiments, the hard carbon precursor is selected from at least one of sucrose, glucose, maltose and starch.
[0045] In certain embodiments, the hard carbon precursor is selected from sucrose.
[0046] In certain embodiments, in step S1, the molar concentration of the hard carbon precursor in the first solvent is 0.2 to 0.5 mol / L, for example, 0.2 mol / L, 0.25 mol / L, 0.3 mol / L, 0.35 mol / L, 0.4 mol / L, 0.45 mol / L or 0.5 mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In certain embodiments, in step S1, the first solvent is selected from at least one of water, methanol, ethanol, ethylene glycol, dimethylformamide and benzene.
[0048] In certain embodiments, in step S1, the first solvent is selected from water.
[0049] In certain embodiments, in step S1, the temperature of the hydrothermal reaction is 150-210°C, for example, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, 200°C, 205°C or 210°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] In certain embodiments, in step S1, the hydrothermal reaction time is 8 to 15 hours, for example, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours, 12 hours, 12.5 hours, 13 hours, 13.5 hours, 14 hours, 14.5 hours or 15 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] In certain embodiments, in step S1, after the hydrothermal reaction is completed, the steps of centrifugation, washing and drying are also included.
[0052] In certain embodiments, the washing is performed by rinsing with distilled water.
[0053] In certain embodiments, the drying time is 1 to 3 hours, such as 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In certain embodiments, the drying temperature is 60-100°C, for example 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In certain embodiments, in step S2, the first protective gas is selected from at least one of argon, helium, krypton and nitrogen.
[0056] In certain embodiments, in step S2, the first protective gas is selected from argon.
[0057] In certain embodiments, in step S2, the temperature of the heat treatment is 1100-1600°C, for example, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C, 1500°C, 1550°C or 1600°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In certain embodiments, in step S2, the heat treatment time is 3 to 7 hours, for example 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours or 7 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In certain embodiments, in step S2, the pickling is performed using hydrochloric acid.
[0060] In certain embodiments, in step S2, the acid washing further includes water washing and drying steps.
[0061] In certain embodiments, the water washing is water washing to neutrality.
[0062] In certain embodiments, in step S3, the mass ratio of the 2,2-dimethylvinylboric acid to the hard carbon material is (3-8):100, such as 3:100, 3.5:100, 4:100, 4.5:100, 5:100, 5.5:100, 6:100, 6.5:100, 7:100, 7.5:100 or 8:100, but not limited to the listed ratios, and other unlisted ratios within the numerical range are also applicable. Thus, it is possible to prevent the artificial SEI film formed due to excessive addition of dimethylvinylboric acid from being too thick, thereby significantly increasing the interface impedance, affecting the insertion and extraction (transmission rate) of sodium ions, and thereby causing the cycle capacity retention rate of the battery using the negative electrode material as the negative electrode active material to decrease; so that the battery equipped with the negative electrode material has a better first coulomb efficiency and cycle performance, as well as lower interface impedance and irreversible capacity decay.
[0063] In certain embodiments, in step S3, the first stirring is stirring until 2,2-dimethylvinylboronic acid is completely dissolved in the second solvent.
[0064] In certain embodiments, in step S3, the second solvent is selected from deionized water.
[0065] In certain embodiments, in step S3, the temperature of the second stirring is 50-70°C, such as 50°C, 55°C, 60°C, 65°C or 70°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0066] In certain embodiments, in step S3, the second stirring is stirring until the solution is evaporated to dryness.
[0067] In certain embodiments, in step S3, the baking temperature is 80 to 120°C, such as 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable. Thus, the B-OH group on the 2,2-dimethylvinylboronic acid can undergo a dehydration reaction with the oxygen-containing functional group on the hard carbon surface, thereby forming a stable chemical bond coated on the hard carbon surface, thereby obtaining a hard carbon negative electrode with a layer of polymer wrapped on the surface, thereby providing conditions for the unsaturated carbon-carbon double bonds on the 2,2-dimethylvinylboronic acid to undergo in-situ electropolymerization to form a polymer network layer during the subsequent charge and discharge process, and finally constructing a hard carbon negative electrode material with an artificial SEI film; so that the battery assembled with the negative electrode material has a better first coulomb efficiency and cycle performance, as well as lower interface impedance and irreversible capacity decay.
[0068] In certain embodiments, in step S3, the baking time is 8 to 12 hours, for example 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours or 12 hours, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0069] [Anode material]
[0070] A second aspect of the present invention provides a negative electrode material, which is prepared according to the method for preparing the negative electrode material provided by the first aspect of the present invention.
[0071] It should be understood that since the negative electrode material provided in the present application is prepared according to the method for preparing the negative electrode material provided in the first aspect of the present invention, the beneficial effects of the method for preparing the negative electrode material described in any of the above embodiments are applicable to the negative electrode material.
[0072] [Negative electrode]
[0073] A third aspect of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the negative electrode material provided by the second aspect of the present invention.
[0074] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The positive electrode current collector can be aluminum foil, copper foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The negative electrode active material layer includes a negative electrode active material. In the present invention, the negative electrode active material is the negative electrode material provided in the second aspect of the present invention.
[0075] The negative electrode active material layer may also include one or two selected from a conductive agent and a binder. The conductive agent is used to improve the conductivity of the electrode. Examples of negative electrode conductive agents include conductive carbon black, conductive graphite, vapor deposited carbon fiber (VGCF), carbon nanotubes, graphene, etc. The binder of the negative electrode improves the bonding performance between the negative electrode active material particles and between the negative electrode active material particles and the current collector. Examples of negative electrode binders include polyvinylidene fluoride (PVDF), styrene-butadiene rubber (SBR), sodium carboxymethyl cellulose (CMC-Na), cyclodextrin, gelatin, polyvinyl alcohol, polyacrylate, acrylonitrile multipolymer, etc. The mass ratio of each component in the negative electrode active material layer can be conventional.
[0076] The present application has no particular restrictions on the preparation method of the negative electrode sheet, and a preparation method known in the art can be selected as long as the purpose of the present application can be achieved. For example, the preparation method of the negative electrode sheet includes but is not limited to the following steps: dispersing the negative electrode active material, the conductive agent, and the binder in a solvent and mixing them to form a uniform negative electrode slurry, coating the negative electrode slurry on the negative electrode collector, and obtaining the negative electrode sheet after drying, cold pressing, cutting, slitting and re-drying. The solvent of the negative electrode slurry can be a conventional solvent in the art, such as deionized water.
[0077] It should be understood that, since the negative electrode plate provided in the present application includes the negative electrode material described in the second aspect of the present invention, the beneficial effects of the method for preparing the negative electrode material described in any of the above embodiments are applicable to the negative electrode plate.
[0078] [Battery]
[0079] A fourth aspect of the present invention provides a battery, comprising the negative electrode plate provided by the third aspect of the present invention.
[0080] In some embodiments, the battery may be a secondary battery or a primary battery, preferably a secondary battery. For example, the battery may be a sodium ion battery, etc., but is not limited thereto. The battery structure of the present application includes but is not limited to a soft-pack sodium ion battery, a square hard-shell battery, or a cylindrical hard-shell battery, etc.
[0081] In some embodiments, the battery further comprises a positive electrode sheet, an electrolyte and a separator. Typically, a battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is disposed between the positive electrode sheet and the negative electrode sheet. During the battery charge and discharge process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive / negative electrode from short-circuiting, while allowing ions to pass through.
[0082] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector. The positive electrode current collector may be aluminum foil, copper foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The positive electrode active material layer includes a positive electrode active material. The positive electrode active material suitable for the present invention may be various known positive electrode active materials that can be used for sodium ion batteries, which can reversibly embed and deintercalate sodium ions. The positive electrode active material may be a sodium ion positive electrode active material commonly used in the art, preferably selected from sodium iron composite oxides (such as NaFeO2), sodium cobalt composite oxides (such as NaCoO2), sodium chromium composite oxides (such as NaCrO2), sodium manganese composite oxides (such as NaMnO2), sodium nickel composite oxides (such as NaNiO2), sodium nickel titanium composite oxides (such as NaNi0 .5 Ti 0.5 O2), sodium nickel manganese composite oxides (such as NaNi 0.5 Mn 0.5 O2), sodium iron manganese composite oxides (such as Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2), sodium nickel cobalt manganese composite oxides (such as NaNi 1 / 3 Co 1 / 3 Mn 1 / 3O2), one or more of sodium iron phosphate compounds (such as NaFePO4), sodium manganese phosphate compounds (such as NaMnPO4) and sodium cobalt phosphate compounds (such as NaCoPO4).
[0083] The positive electrode active material layer may also include one or two selected from a conductive agent and a binder. The conductive agent is used to improve the conductivity of the electrode. Examples of the conductive agent of the positive electrode include one or more of conductive carbon black, carbon fiber (CF), acetylene black, Ketjen black, graphene, carbon nanotubes and carbon microspheres. The binder of the positive electrode improves the bonding performance between the positive electrode active material particles and between the positive electrode active material particles and the current collector. Examples of the binder of the positive electrode include at least one of a fluorine-containing resin, a polypropylene resin, a fiber-type binder, a rubber-type binder and a polyimide-type binder. The mass ratio of each component in the positive electrode active material layer can be conventional.
[0084] The positive electrode active material layer is obtained by coating a positive electrode slurry containing various components of the positive electrode active material layer and a solvent onto a positive electrode current collector, and then rolling and slitting. The solvent of the positive electrode slurry can be N-methylpyrrolidone (NMP).
[0085] The separator can be a polymer porous separator, an inorganic porous separator or a polymer-inorganic composite porous separator. The polymer porous separator includes a single-layer polymer porous separator and a multi-layer polymer porous separator.
[0086] The electrolyte generally comprises a solvent and a sodium salt. The electrolyte suitable for the present invention may be conventional, for example, the solvent may be one or more selected from dimethyl carbonate (DMC), propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC) or 1,4-butyl propyl ester, more preferably one or more of PC, EC and EMC. The sodium salt may be one or more selected from sodium tetrafluoroborate, sodium hexafluorophosphate, sodium trifluoromethanesulfonate or sodium perchlorate.
[0087] The battery of the present application also includes a packaging shell for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in a sodium ion battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging shell, and it can be a packaging shell known in the art, as long as it can achieve the purpose of the present application.
[0088] The present invention has no special limitation on the method for preparing the battery, and the technical scheme for preparing the negative electrode material into a battery such as a secondary battery, which is well known to those skilled in the art, can be adopted.
[0089] It should be understood that, since the battery provided in the present application includes the negative electrode plate described in the third aspect of the present invention, the beneficial effects of the method for preparing the negative electrode material described in any of the above embodiments are applicable to the battery.
[0090] [Electronic devices]
[0091] A fifth aspect of the present invention provides an electronic device, comprising the battery provided by the fourth aspect of the present invention.
[0092] The use of the battery of the present application is not particularly limited, and it can be used in any electronic device known in the prior art. In some embodiments, the battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, drones, and sodium ion capacitors, etc.
[0093] It should be understood that, since the electronic device provided in the present application includes the battery described in the fourth aspect of the present invention, the beneficial effects of the method for preparing the negative electrode material described in any of the above embodiments are applicable to the electronic device.
[0094] The method of the present invention is described below by means of specific examples. It should be understood that these examples are used to illustrate the basic principles, main features and advantages of the present invention, and the present invention is not limited to the scope of the following examples; the implementation conditions adopted in the examples can be further adjusted according to specific requirements, and the implementation conditions not specified are usually the conditions in routine experiments.
[0095] Example 1
[0096] S101: First, 0.03 mol of sucrose (hard carbon precursor) was dissolved in 100 mL of water to obtain 100 ml of 0.3 mol / L sucrose solution, which was added to a high-pressure reactor and subjected to a hydrothermal reaction in the reactor at a reaction temperature of 180° C. for 10 h. After the reaction was completed, the reaction product was separated on a centrifuge and repeatedly washed with distilled water for several times. The collected reaction product was placed in a vacuum oven at 80° C. and dried for 2 h to obtain a precursor powder (i.e., intermediate A);
[0097] S102: Put the precursor powder (i.e., intermediate A) obtained in step S101 into a tubular furnace, introduce argon protection, heat to 1300° C. and keep warm for 5 hours, take out, pickle with hydrochloric acid and then wash with water until neutral, and dry to obtain a hard carbon material;
[0098] S103: Add 5 g of 2,2-dimethylvinylboric acid into deionized water and stir for 30 minutes. After complete dissolution, add 100 g of the hard carbon material obtained in step S102 and stir at high speed at 60°C until the solution is evaporated. Then, place the evaporated product in a vacuum oven at 100°C and bake it for 10 hours. After taking it out, a hard carbon negative electrode material (i.e., negative electrode material) with an artificial SEI film is prepared.
[0099] Example 2
[0100] The only difference between this embodiment and embodiment 1 is that the added amount of 2,2-dimethylvinylboronic acid is 3 g.
[0101] Example 3
[0102] The only difference between this embodiment and embodiment 1 is that the amount of 2,2-dimethylvinylboronic acid added is 8 g.
[0103] Example 4
[0104] The only difference between this embodiment and embodiment 1 is that the amount of 2,2-dimethylvinylboronic acid added is 10 g.
[0105] Comparative Example
[0106] The only difference between the comparative example and Example 1 is that the comparative example does not include step S103 in Example 1, and the hard carbon material is prepared only by steps S101 and S102 in Example 1.
[0107] Electrochemical performance test
[0108] Sodium ion battery preparation:
[0109] (1) Preparation of negative electrode sheet: The hard carbon negative electrode material with artificial SEI film in Examples 1 to 4 and the hard carbon material in the comparative example were uniformly mixed with conductive carbon black (SP), carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) at a mass ratio of 94.6:2:1:2.4, and uniformly coated on the negative electrode current collector (Cu foil) on a transfer coater, and rolled and sliced to form a negative electrode sheet;
[0110] (2) Preparation of positive electrode sheet: layered oxide sodium iron manganate, conductive carbon black (SP), carbon nanotubes (CNT) and polyvinylidene fluoride (PVDF) were uniformly mixed in a mass ratio of 97:1.2:0.8:1, uniformly coated on the positive electrode collector (aluminum foil) on a transfer coater, and rolled and sliced to form a positive electrode sheet;
[0111] (3) Diaphragm: The diaphragm uses a PE film as the base film, the thickness of the base film is 9 μm, a single-sided gravure coating of an aluminum oxide layer with a thickness of 3 μm, and then a double-sided coating of a PVDF layer with a thickness of 3 μm;
[0112] (4) Electrolyte: NaPF6 was dissolved in a mixed solvent of ethylene carbonate, ethyl methyl carbonate and diethyl carbonate in a ratio of 1.5:1:0.5, and mixed evenly to obtain an electrolyte; wherein the concentration of NaPF6 was 1.2 mol / L;
[0113] (5) Battery assembly: The prepared negative electrode sheet, positive electrode sheet and separator are wound to obtain a battery cell, and the battery cell is placed in a battery case, dried, injected with electrolyte, packaged, formed, and divided into different volumes, thereby obtaining a sodium ion battery comprising the hard carbon negative electrode material with an artificial SEI film in Examples 1 to 4 and the hard carbon material in the comparative example.
[0114] The sodium ion batteries prepared according to the above method were tested in turn as follows:
[0115] 1. Test of first discharge capacity, first charge capacity and first coulomb efficiency: During formation, charge to 3.4V at 0.05C constant current, let stand for 5 minutes, then charge to 3.75V at 0.1C; during capacity division, charge to 4V at 0.2C constant current and constant voltage, cut-off current is 0.05C, let stand for 5 minutes, record the capacity at this time as the first charge capacity C0; then discharge to 2V at 0.2C constant current, record the discharge capacity at this time as the first discharge capacity C1; first coulomb efficiency = C1 / C0*100%. The test results are shown in Table 1.
[0116] Table 1
[0117] Example First charge capacity mAh / g First discharge capacity mAh / g First coulombic efficiency % Example 1 138.7 120 86.5% Example 2 132.4 112 84.6% Example 3 134.6 115.7 86.0% Example 4 130.8 110 84.1% Comparative Example 135 106.9 79.2%
[0118] As can be seen from Table 1, the battery prepared with the negative electrode material in Example 1 exhibits the most excellent first coulombic efficiency, which is 9.2% higher than the first efficiency of the comparative example, and the first discharge capacity is increased by 12.3%, which indicates that the construction of the artificial SEI film has a significant improvement effect on the first efficiency of the battery and can significantly improve the electrochemical performance of the battery. In addition, Example 4 exhibits a lower first efficiency than Examples 1 to 3, because excessive addition of dimethylvinylboric acid will cause the artificial SEI film to be too thick, which is not conducive to the embedding and extraction of sodium ions, thereby resulting in a decrease in discharge capacity and first efficiency.
[0119] 2. Capacity retention rate test: At 25°C, charge to 4V at 0.5C constant current and constant voltage, with a cut-off current of 0.05C, and let stand for 5 minutes; discharge to 2V at 0.5C constant current, let stand for 5 minutes, and record the discharge capacity at this time as the initial discharge capacity C3, which is one cycle; repeat the process for 200 cycles and record the discharge capacity Cn after each cycle (where n is the number of cycles), and the capacity retention rate of each cycle = Cn / C3*100% (where n is the number of cycles). The capacity retention rate line graph during the cycle is as shown in the attached figure. Figure 1As shown; the capacity retention rate after the 200th cycle = C200 / C3*100%, and the results are shown in Table 2.
[0120] 3. Battery DC internal resistance (DCR) test: At 25°C, charge to 4V with 0.05C constant current and constant voltage, the cut-off current is 0.05C, and stand for 5min; discharge to 2V with 0.05C constant current, and stand for 5min, this is one cycle; after repeating this process for 200 cycles, test the DCR of the battery at 50% SOC (State of Charge), specifically: first charge to 4V with 0.5C constant current and constant voltage, the cut-off current is 0.05C, and stand for 5min; discharge with 0.5C constant current for 60min, stand for 30min, the voltage is recorded as U0, discharge with 2C constant current for 30s, the voltage is recorded as U1, DCR = (U0-U1) / current, the results are shown in Table 2.
[0121] Table 2
[0122] Example Capacity retention rate (%) DCR(mΩ) Example 1 94.6% 42 Example 2 91.7% 46.3 Example 3 92.6% 47.2 Example 4 90.6% 55.1 Comparative Example 89.3% 68.9
[0123] As can be seen from Table 2, the 200-cycle cycle retention rate of the sodium ion battery using the negative electrode materials of Examples 1 to 3 as the negative electrode active material is all above 91.5%, and the battery DCR after 200 cycles is small and is within 50mΩ, which has excellent cycle stability. Compared with Example 4, the 200-cycle cycle retention rate of the material of Example 1 is increased by 4.4%, and the DCR is reduced by 23.8%, which shows that when the ratio of 2,2-dimethylvinylboric acid to the hard carbon material obtained in step S102 is controlled at (3 to 8): 100, the prepared negative electrode material can make the battery have better resistance to capacity decay (i.e., longer service life) and cycle stability. It further shows that excessive addition of dimethylvinylboric acid will lead to an excessively thick artificial SEI film, which will significantly increase the interface impedance, which is not conducive to sodium ion transmission, and thus leads to a decrease in the cycle retention rate. In addition, compared with the comparative example, the 200-cycle cycle retention rate of the material in Example 1 was increased by 5.9%, and the DCR was reduced by 39%, which indicates that the artificial SEI film in the embodiment of the present invention is more stable and less susceptible to damage than the naturally formed SEI film, which reduces the irreversible capacity decay of the battery and significantly reduces the impedance of the interface, so that the battery exhibits excellent cycle stability.
[0124] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.
Claims
1. A method for preparing a negative electrode material, characterized in that: The method for preparing the negative electrode material comprises the following steps: S1: dissolving a hard carbon precursor in a first solvent and performing a hydrothermal reaction to obtain an intermediate A; S2: heat-treating and pickling the intermediate A obtained in step S1 under a first protective gas atmosphere to obtain a hard carbon material; S3: Add 2,2-dimethylvinylboric acid to the second solvent, stir for the first time, then add the hard carbon material obtained in step S2, stir for the second time, and bake to obtain the negative electrode material.
2. The method for preparing the negative electrode material according to claim 1, characterized in that: The hard carbon precursor is selected from at least one of sucrose, glucose, maltose and starch.
3. The method for preparing the negative electrode material according to claim 1, characterized in that: In step S1, the molar concentration of the hard carbon precursor in the first solvent is 0.2-0.5 mol / L; The first solvent is selected from at least one of water, methanol, ethanol, ethylene glycol, dimethylformamide and benzene; The temperature of the hydrothermal reaction is 150-210° C., and the time of the hydrothermal reaction is 8-15 hours.
4. The method for preparing the negative electrode material according to claim 1, characterized in that: In step S1, after the hydrothermal reaction is completed, the steps of centrifugation, washing and drying are also included; Preferably, the drying temperature is 60-100° C., and the drying time is 1-3 hours.
5. The method for preparing the negative electrode material according to claim 1, characterized in that: In step S2, the first protective gas is selected from at least one of argon, helium, krypton and nitrogen; The heat treatment temperature is 1100-1600°C, and the heat treatment time is 3-7 hours; Preferably, the acid washing further includes water washing and drying steps; the water washing is to neutralize the acid.
6. The method for preparing the negative electrode material according to claim 1, characterized in that: In step S3, the mass ratio of the 2,2-dimethylvinylboric acid to the hard carbon material is (3-8):100; The first stirring is stirring until 2,2-dimethylvinylboronic acid is completely dissolved in the second solvent.
7. The method for preparing the negative electrode material according to claim 1, characterized in that: In step S3, the temperature of the second stirring is 50-70° C.; the second stirring is stirring until the solution is evaporated to dryness; The baking temperature is 80-120° C., and the baking time is 8-12 hours.
8. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode material, and the negative electrode material is prepared according to the method for preparing a negative electrode material according to any one of claims 1-7.
9. A battery, characterized in that: The battery comprises the negative electrode sheet as claimed in claim 8.
10. An electronic device, characterized in that: The electronic device comprises the battery as claimed in claim 9.
Citation Information
Patent Citations
Monodisperse core-shell structure polymer nano particle as well as preparation and application thereof
CN103304732A
Electrode pole piece and lithium ion secondary battery containing same
CN111933944A
Sodium-ion battery electrode material pre-SEI film hard carbon material and application thereof
CN115036468A
Sodium ion battery and modified hard carbon negative electrode thereof
CN115947336A
Interface modified sodium ion battery hard carbon negative electrode material / negative electrode, preparation method and application
CN117317153A
Cited By
Boron-containing compound modified lithium ion battery hard carbon negative electrode material as well as preparation method and application thereof
CN121672494A